2015
DOI: 10.1111/jsm.12865
|View full text |Cite
|
Sign up to set email alerts
|

Hypersexuality and High Sexual Desire: Exploring the Structure of Problematic Sexuality

Abstract: Introduction The concept of hypersexuality has been accompanied by fierce debates and conflicting conclusions about its nature. One of the central questions under the discussion is a potential overlap between hypersexuality and high sexual desire. With the relevant research in its early phase, the structure of hypersexuality remains largely unknown. Aim The aim of the present study was to systematically explore the overlap be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…Accordingly, the construct of Sexual Addiction/ Hypersexual Disorder displays problematic behaviors including: excessive masturbation, cybersex, pornography use, aberrant sexual behavior with consenting adults, telephone sex, strip club visitation, and other addictive behaviors [ 98 ]. Certainly we agree that there may be distinct differences between sexual addiction and hypersexuality as noted by Carvalho, et al [ 99 ], Rettenberger, et al [ 100 ], Kor, et al [ 1 ], Reid, et al [ 9 ], Kafka and Hennen [ 13 ], and Prause, et al [ 93 - 94 ] amongst others.…”
Section: Reviewsupporting
confidence: 79%
“…Accordingly, the construct of Sexual Addiction/ Hypersexual Disorder displays problematic behaviors including: excessive masturbation, cybersex, pornography use, aberrant sexual behavior with consenting adults, telephone sex, strip club visitation, and other addictive behaviors [ 98 ]. Certainly we agree that there may be distinct differences between sexual addiction and hypersexuality as noted by Carvalho, et al [ 99 ], Rettenberger, et al [ 100 ], Kor, et al [ 1 ], Reid, et al [ 9 ], Kafka and Hennen [ 13 ], and Prause, et al [ 93 - 94 ] amongst others.…”
Section: Reviewsupporting
confidence: 79%
“…Furthermore, the personality traits low impulse control, negative self-image, affective instability, and dysphoric mood have also been found to be positively related to hypersexuality (Carvalho, Stulhofer, Vieira, & Jurin, 2015;Chaney & Burns-Wortham, 2014;Kalichman & Rompa, 1995;Lloyd, Raymond, Miner, & Coleman, 2007;Reid, Bramen, Anderson, & Cohen, 2014;Reid, Carpenter, Gilliland, & Karim, 2011). Griffin et al (2016) found a negative relationship between sexual self-esteem and hypersexual behavior.…”
Section: Personality Factorsmentioning
confidence: 97%
“…In a large sample of Croatian adults, cluster analysis identified two meaningful clusters, one representing problematic sexuality and another reflecting high sexual desire and frequent sexual activity. Individuals in the problematic cluster reported more psychopathology compared to individuals in the high-desire/frequent-activity cluster (95). This suggests CSB may be organized more along a continuum of increasing sexual frequency and preoccupation, in which clinical cases are more likely to occur in the upper end of the continuum or dimension (96).…”
Section: Assessment and Treatment Of Csbmentioning
confidence: 99%